Rancang Bangun Sistem Pemesanan Hotel Pada TX Travel Sriwijaya Di Lombok - Baadilla, Muhammad Haidar; Lusiani, Titik; Churniawan, Agus Dwi (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2017)
Hotel booking system on the TX Travel Sriwijaya yet have a booking system that supports the activities of the booking. Thus, the customer and admin still takes a long time in the hotel determination according to customer requirements. Based on these problems required an application that aims to speed up hotel reservations for prospective customers to display options required in areas of potential customers. In such applications, potential customers can perform a search based on location, price, and type of rooms required. making this application using SDLC. According to O'Brien (2005), the definition of System Development Life Cycle (SDLC) is a system development cycle that serves to illustrate the main stages and steps of each stage. According to Dennis, Wixom & Roth (2012) SDLC is the process of determining how information systems can support business needs.